MEMUKUL ISTERI YANG NUSYUZ; ANTARA UPAYA PENDIDIKAN DALAM ISLAM DAN KEKERASAN DALAM RUMAH TANGGA - Hasiah & Rukmana Prasetyo (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2021)
This article describes the husband's actions in educating his wife, especially against nusyuz wives, because in this case it often happens that a husband beats his nusyuz wife. This action reaps the pros and cons in the community for that the author feels challenged to examine this action from the perspective of Islam and Domestic Violence (KDRT). To find this answer, the author uses the library method, which is to browse the literature related to the topic and then explain the most dominant side.The findings in the search show that the act of hitting a wife who is nusyuz has two different sides, if the hit is physical with a hard hit, it will occupy an act that includes Domestic Violence (KDRT). However, if the light stroke that does not leave a trace is only a lesson, even so that this kind of hitting is the last alternative to educate the wife.